192k views
2 votes

(12x-3)/(12)=(12x+3)/(8)
and the answer is
(-5)/(4)

1 Answer

6 votes

Answer:


\sf x = -(5)/(4) \qquad or \qquad -1(1)/(4)

Explanation:

Given expression:


\sf (12x-3)/(12) = (12x+3)/(8)

Cross multiply:


\sf 8(12x-3)= 12(12x+3)

Distribute inside parenthesis:


\sf 96x-24= 144x+36

Collect like terms in one side:


\sf 96x-144x= 36+24

Simplify following:


\sf -48x= 60

Divide both sides by -48:


\sf (-48x)/(-48) = (60)/(-48)

Simplify following:


\sf x = -(5)/(4) \:\ (improper\ fraction) \qquad or \qquad -1(1)/(4) \ (mixed \:\ fraction)

User Quest Monger
by
6.3k points